2016
DOI: 10.5194/os-12-185-2016
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Somali Current eddies during the summer monsoon: insights from a numerical study

Abstract: Abstract. Three hindcast simulations of the global ocean circulation differing by resolution (1/4 or 1/12• ) or parametrization or atmospheric forcing are used to describe the interactions between the large anticyclonic eddies generated by the Somali Current system during the Southwest Monsoon. The present investigation of the Somalian coherent eddy structures allows us to identify the origin and the subsequent development of the cyclones flanked upon the Great Whirl (GW) previously identified by Beal and Dono… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Upwelled waters are then recirculated by large-scale circulation and mesoscale features. Climatological summer SLA (Figure 1a) clearly reveals strong quasi-permanent eddies like the Great Whirl around 52°E and 9°N and the Socotra Eddy to its northeast (Akuetevi et al, 2016;Beal & Donohue, 2013;Trott et al, 2018;Figure 1a,b). Additionally, the SSS field reveals low salinity values within the Great Whirl with the Arabian Sea high salinity water mass about its exterior (Beal & Donohue, 2013; Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Upwelled waters are then recirculated by large-scale circulation and mesoscale features. Climatological summer SLA (Figure 1a) clearly reveals strong quasi-permanent eddies like the Great Whirl around 52°E and 9°N and the Socotra Eddy to its northeast (Akuetevi et al, 2016;Beal & Donohue, 2013;Trott et al, 2018;Figure 1a,b). Additionally, the SSS field reveals low salinity values within the Great Whirl with the Arabian Sea high salinity water mass about its exterior (Beal & Donohue, 2013; Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…For eddies having maximum amplitudes above 40 cm, CEs along the Somali Current region tend to propagate in a clockwise trajectory as they displace about the larger-radius AEs (Jensen, 1991;Matsuura & Yamagata, 1982). Akuetevi et al (2016) describes this phenomenon of an asymmetric dipole where smaller cyclonic eddies generated by cyclonic vorticity bursts characteristic of a low-latitude western boundary current circle about their larger-radius counterparts (AEs). During the 22-year period of study, more CE trajectories (seven) than AE trajectories (two) were observed with maximum amplitudes greater than 40 cm (Figures 4j and 4k respectively, 10-20, 20-30, 30-40, and > 40 cm).…”
Section: 1029/2018gl078381mentioning
confidence: 99%
“…Large anticyclonic eddies like the Great Whirl and Socotra Eddy have been known to advect smaller cyclonic dipoles whose low SSHs are sourced from upwelled waters along the Somali Coast and Arabian Peninsula (Akuetevi et al, ; Beal & Donohue, ). For this reason, large anticyclonic eddies in this region have been observed to coalesce (Akuetevi et al, ; Schott et al, ), which explains the decreasing number of anticyclonic eddies following the second week of July (Figure a) while maintaining overall larger radii and smaller amplitudes (which are so strong in cyclonic eddies along upwelling zones). Trott et al () found a higher number of large anticyclonic eddies (with amplitudes greater than 20 cm) in the Arabian Sea during stronger monsoon seasons.…”
Section: Resultsmentioning
confidence: 99%